Pemanfaatan Game Scratch sebagai Media Pembelajaran Interaktif di SD Inpres Waharia - Gunawan Prayitno; Merlin Tandi Pakila; Arief Rahman Hakim (Jurnal Publikasi Teknik Informatika, 2025)
Low student learning motivation in conventional teaching remains a major challenge in elementary education, especially in regions with limited access to educational technology. This study aims to develop and evaluate the effectiveness of interactive learning media based on games created with the Scratch application to improve learning motivation among fourth-grade students at SD Inpres Waharia. The research employed a Research and Development (R&D) approach with a prototyping model, encompassing stages of needs analysis, media design, prototyping, implementation, and evaluation through limited trials. Data collection involved student engagement observations, teacher interviews, and validation sheets from media and subject experts. The results indicated that the use of Scratch significantly enhanced students’ attention and active participation, creating a more enjoyable and engaging learning atmosphere. Teachers acknowledged that the media supported visual and interactive material delivery, accelerating students’ understanding of key concepts. Therefore, Scratch-based media is a promising alternative for innovative learning tools, aligning with 21st-century educational needs and supporting digital transformation policies in elementary education.